L’analyse géopolitique du terrorisme : conditions théoriques et conceptuelles - Daniel Dory (L'Espace Politique)
This paper presents a theoretical approach to the conditions for a geopolitical analysis of terrorism. Starting with a review of the main advances in the geographic and geopolitical literature dealing with the topic, it proceeds to discuss the two main obstacles -definitional end empirical- that all research in this field must deal with, insisting in the specific nature of terrorism as a technique of use and management of political violence. A systemic analytical framework is then proposed, based on the elements and relations composing the terrorist complex, which is only fully understandable when included in a sequence taking its roots in the different forms of dissidence and evolving towards the dynamic logic of insurrections. Finally, the main aspects of the emergence of terrorism as a global problem are briefly commented.